1999
DOI: 10.1016/s1098-7339(99)90101-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative therapeutic evaluation of intrathecal versus epidural methylprednisolone for long-term analgesia in patients with intractable postherpetic neuralgia*1

Abstract: Our results suggest the effectiveness of intrathecal as compared to epidural MPA for relieving the pain and allodynia associated with PHN. Also, our findings, together with the decrease in IL-8, may indicate that intrathecal MPA improves analgesia by decreasing an ongoing inflammatory reaction in the CSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Four trials were comparator studies without a placebo group and therefore could not be included in the meta-analysis. These trials compared amitriptyline to nortriptyline [30], amitriptyline to maprotiline [31], and intrathecal steroid to epidural steroid [17] and two doses of levorphanol [21]. Of the remaining 31 trials, we were able to extract dichotomous outcome data for efficacy meta-analysis from 25 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four trials were comparator studies without a placebo group and therefore could not be included in the meta-analysis. These trials compared amitriptyline to nortriptyline [30], amitriptyline to maprotiline [31], and intrathecal steroid to epidural steroid [17] and two doses of levorphanol [21]. Of the remaining 31 trials, we were able to extract dichotomous outcome data for efficacy meta-analysis from 25 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In the vast majority of trials, this was only until the end of the treatment period, with the exception of the intrathecal methylprednisolone studies [16,17] that reported follow-up periods to 24 wk and 2 y, and one study that examined amitriptyline and followed ten “good responders” for 2 y [31]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first, intrathecal administration of methylprednisolone was more effective than epidural administration [66], but the sample size was only 25 patients divided into the two arms. Subsequently, the same researchers reported efficacy over 1–2 years for four intrathecal injections of methylprednisolone and lidocaine performed over one month compared with lidocaine alone and with a no treatment control group [69].…”
Section: Peripheral Np Conditionsmentioning
confidence: 99%